Bowenoid Papulosis A Case Report - Handelia Phinari; Ni Nyoman Ayu Sutrini (Jurnal Profesi Medika, 2022)
Bowenoid papulosis (BP) is a rare sexually transmitted disease caused by Human Papillomavirus 16 that affect young sexually active age group.